2020
DOI: 10.26480/taec.01.2020.15.18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Plastic Packaging on Postharvest Quality of Tomato (Lycopersicon Esculentum Mill.)

Abstract: Tomato is highly perishable in nature and incurred high post-harvest losses due to unsuitable packaging method. Experimentation was undertaken to find the effect of different polymeric film packaging on postharvest quality of tomato var. Manisha in a completely randomized block design (CRD). There was five treatment viz. open, ordinary plastic, Polypropylene (PP38,) Low-Density Polyethylene (LDPE38) and 25) which was replicated four times. Destructive and non-destructive samples were prepared for each treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…The smallest decrease in TC was observed in the control during storage -from 0.78% to 0.61% and when treated with MPP from 0.78% to 0.58% of Avgustin tomatoes during storage for 15 days. Previous studies [10] reported that packaging significantly affects TA, which decreases in fruits, while pH increases as fruits are stored. With increasing storage time, TC decreased, with the highest TC values recorded on day 0 (0.51%), and the lowest TC values on day 28 (0.30%) [11].…”
Section: Resultsmentioning
confidence: 92%
“…The smallest decrease in TC was observed in the control during storage -from 0.78% to 0.61% and when treated with MPP from 0.78% to 0.58% of Avgustin tomatoes during storage for 15 days. Previous studies [10] reported that packaging significantly affects TA, which decreases in fruits, while pH increases as fruits are stored. With increasing storage time, TC decreased, with the highest TC values recorded on day 0 (0.51%), and the lowest TC values on day 28 (0.30%) [11].…”
Section: Resultsmentioning
confidence: 92%
“…The stage of ripening decreased sharply from 10 to 19 days after harvest due to softening of the fruit structure (Figure 3). According to Adhikari et al (2020), a sharp decrease in firmness during ripening is also caused by increased metabolic activity in fruit tissue. Fruit ripening is associated with an increase in the polygalacturonase (PG) enzyme in the fruit which causes cell wall degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Ref. [32] explained that the pH value of tomatoes increases with the storage time due to ripening and respiration. The pH values ranged from 4.20 to 4.60 over the 28-day storage period, as presented in Table 3.…”
Section: Ph Valuementioning
confidence: 99%
“…Ref. [32] reported that the packaging significantly affects the TA and that the TA decreases in the fruit, while the pH increases as the fruit storage time progress toward senescence. Tomato samples packaged and stored under cold storage conditions had higher TA values, with an average of 0.42%, than the TA values averaging 0.36% of tomato samples stored under ambient storage conditions.…”
Section: Titratable Aciditymentioning
confidence: 99%